2014
DOI: 10.3390/land3030793
|View full text |Cite
|
Sign up to set email alerts
|

Climate–Human–Land Interactions: A Review of Major Modelling Approaches

Abstract: International agreements on climate change have highlighted the role of land in climate and human dynamics, making it an issue of global importance. The modelling of land-related processes, sectors, and activities has recently become a central topic in economic and policy theory, as well as within environmental sciences. Modelling strategies have been improved and new datasets have come into light for land-cover and land-use change analysis. However, unexpected human behavior and natural constraints challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 169 publications
(171 reference statements)
1
24
0
Order By: Relevance
“…From some existing reviews [10,[31][32][33][34][35][36][37][38][39][40][41][42][43][44] on modelling applications and approaches in land systems that were published between 2002 and 2016, we found that the concept of feedback has received increasing attention and has been made more explicit (for details see Table S1). However, the knowledge on feedback representation in land models is still lacking, even though it has been suggested that those models were under way [31].…”
Section: Introductionmentioning
confidence: 99%
“…From some existing reviews [10,[31][32][33][34][35][36][37][38][39][40][41][42][43][44] on modelling applications and approaches in land systems that were published between 2002 and 2016, we found that the concept of feedback has received increasing attention and has been made more explicit (for details see Table S1). However, the knowledge on feedback representation in land models is still lacking, even though it has been suggested that those models were under way [31].…”
Section: Introductionmentioning
confidence: 99%
“…The latter is physically designed and related to vegetation (natural or artificially modified) and its structure, as well as the other land types covering terrestrial land. The relation between these two disciplines is such that land cover may have multiple land uses, and land use affects the land cover [1]. Global land use has been changed significantly in the past three decades due to population growth and its footprints.…”
Section: Introductionmentioning
confidence: 99%
“…In general, individuals and firms are modelled as representative agents within, respectively, one region and one market sector. This implies assuming the same socio-economic types of preferences across the world and across economies (Michetti and Zampieri, 2014). As an alternative we consider market issues directly through incomes at farm level which may reveal another part of the picture.…”
Section: Introductionmentioning
confidence: 99%